PENGARUH STRUKTUR ORGANISASI, FASILITAS KERJA DAN BEBAN KERJA TERHADAP EFEKTIVITAS KERJA PEGAWAI BPR CHANDRA MUKTIARTHA YOGYAKARTA - Inayat Hanum Indriati (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
The study is to determine the effect of organizational structure, work facilities and workload, either simultaneously or partially on the work effectiveness of BPR Chandra Muktiartha Yogyakarta employees.The sample of this research is all employees of BPR Chandra Muktiartha Yogyakarta, totaling 140 people who were selected by using population sampling technique. The data collected with a questionnaire. Analysis technique used multiple linear regression analysis.The results that (1) the organizational structure has a significant effect on the work effectiveness of BPR Chandra Muktiartha Yogyakarta employees (p = 0.000); (2) Work facilities have a significant effect on the work effectiveness of BPR Chandra Muktiartha Yogyakarta employees (p = 0.035); (3) Workload has a significant effect on the work effectiveness of BPR Chandra Muktiartha Yogyakarta employees (p = 0.003); (4) The organizational structure, work facilities and workload simultaneously affect the work effectiveness of BPR Chandra Muktiartha Yogyakarta employees (p = 0.000).